Changes in soil bacterial communities and nitrogen mineralization with understory vegetation in boreal larch forests. (March 2022) - Xiao, Ruihan; Man, Xiuling; Duan, Beixing; Cai, Tijiu; Ge, Zhaoxin; Li, Xuefei; Vesala, Timo
Abstract: Plant community composition can alter soil microbial community structure and function, and further influence the process of soil N transformation. However, this effect is rarely noticed in forest types characterized by understory vegetation, especially in N-limited boreal forests where the understory vegetation substantially contributes to soil nutrient cycling. To investigate whether forest types characterized by understory vegetation can affect soil N mineralization and bacterial community, we determined mineral N contents, net N mineralization rates, soil bacterial community and microbial biomass in soils under three types of larch forest ( Sphagnum - Bryum - Rhododendron tomentosum (previously: Ledum palustre) - Larix gmelinii forest(SLL), Rhododendron dauricum - Larix gmelinii forest (RL), and Rhododendron tomentosum - Larix gmelinii forest (LL)) in the typical boreal climatic region in northeast China. We found that soil N availability, soil N mineralization rates, soil bacterial community and microbial biomass vary with the difference of the understory vegetation, and these changes were stronger in the 0–10 cm soil layer than in the 10–20 cm soil layer. In addition, compared with soil N content, soil microbial biomass was more strongly correlated with soil N mineralization. Structural equation modeling was used to analyze the effects of driving factors and pathways on soil N dynamics. The results suggested that soil N mineralization was related to forest type and soil microbial biomass, while soil microbial biomass was significantly affected by soil bacterial composition. Finally, abundances of Actinobacteria, Patescibacteria and Chloroflexi were significantly correlated with soil N mineralization. Together, these mechanisms provide insight into the important function of understory vegetation in the process of soil N cycling in the boreal region. Highlights: In boreal larch forest ecosystems, soil microbial communities and nitrogen transformation varies with the difference of the understory vegetation. The changes were more pronounced in the 0–10 cm soil layer than the 10–20 cm soil layer. The variation in abundance of Actinobacteria, Patescibacteria, and Chloroflexi had significant effects on soil nitrogen mineralization. No direct effects of soil bacterial composition on soil nitrogen mineralization were found among different larch forests.